SPARC–Dependent Cardiomyopathy in Drosophila. (April 2016) - Hartley, Paul S.; Motamedchaboki, Khatereh; Bodmer, Rolf; Ocorr, Karen
Abstract : Background—: The Drosophila heart is an important model for studying the genetics underpinning mammalian cardiac function. The system comprises contractile cardiomyocytes, adjacent to which are pairs of highly endocytic pericardial nephrocytes that modulate cardiac function by uncharacterized mechanisms. Identifying these mechanisms and the molecules involved is important because they may be relevant to human cardiac physiology. Methods and Results—: This work aimed to identify circulating cardiomodulatory factors of potential relevance to humans using the Drosophila nephrocyte–cardiomyocyte system. A Kruppel-like factor 15 ( dKlf15 ) loss-of-function strategy was used to ablate nephrocytes and then heart function and the hemolymph proteome were analyzed. Ablation of nephrocytes led to a severe cardiomyopathy characterized by a lengthening of diastolic interval. Rendering adult nephrocytes dysfunctional by disrupting their endocytic function or temporally conditional knockdown of dKlf15 led to a similar cardiomyopathy. Proteomics revealed that nephrocytes regulate the circulating levels of many secreted proteins, the most notable of which was the evolutionarily conserved matricellular protein Secreted Protein Acidic and Rich in Cysteine (SPARC), a protein involved in mammalian cardiac function. Finally, reducing SPARC gene dosage ameliorated the cardiomyopathy that developed in the absence of nephrocytes. Conclusions—: The data implicate SPARC in the noncell autonomous control of cardiac function in Drosophila and suggest that modulation of SPARC gene expression may ameliorate cardiac dysfunction in humans. Abstract : Supplemental Digital Content is available in the text.